Mapping migration in a songbird using high‐resolution genetic markers. Issue 23 (December 2014) - Ruegg, Kristen C.; Anderson, Eric C.; Paxton, Kristina L.; Apkenas, Vanessa; Lao, Sirena; Siegel, Rodney B.; DeSante, David F.; Moore, Frank; Smith, Thomas B.
Abstract Neotropic migratory birds are declining across the Western Hemisphere, but conservation efforts have been hampered by the inability to assess where migrants are most limited—the breeding grounds, migratory stopover sites or wintering areas. A major challenge has been the lack of an efficient, reliable and broadly applicable method for measuring the strength of migratory connections between populations across the annual cycle. Here, we show how high‐resolution genetic markers can be used to identify genetically distinct groups of a migratory bird, the Wilson's warbler (Cardellina pusilla), at fine enough spatial scales to facilitate assessing regional drivers of demographic trends. By screening 1626 samples using 96 highly divergent single nucleotide polymorphisms selected from a large pool of candidates ( 450 000), we identify novel region‐specific migratory routes and timetables of migration along the Pacific Flyway. Our results illustrate that high‐resolution genetic markers are more reliable, precise and amenable to high throughput screening than previously described intrinsic marking techniques, making them broadly applicable to large‐scale monitoring and conservation of migratory organisms.